2010
DOI: 10.1111/j.1365-2583.2009.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

A cathepsin L‐like proteinase is involved in moulting and metamorphosis in Helicoverpa armigera

Abstract: Holometabolous insects undergo larval moulting and metamorphosis within their life cycle. A cDNA encoding the cathepsin L-like proteinase Ha-cathL has been cloned from Helicoverpa armigera. It has a sequence of 1826 bp and encodes a 550-residue protein with a molecular mass of 63 kDa. Northern blot analysis indicated that Ha-cathL is specifically expressed in haemocytes, with increased expression during larval moulting and metamorphosis. In vivo experimentation revealed that Ha-cathL is up-regulated by 20-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 34 publications
(47 reference statements)
2
40
1
Order By: Relevance
“…Our data showed that most silkworm papain-like cysteine proteases genes are highly expressed in metamorphosis not only in wandering stage involving in molting and metamorphosis 17,18 but also in later pupa stage and adult cuticle formation stage, which are highly correlated to the digestion time scale of B. mori arylphorin in vivo [ Fig. 5(D)].…”
Section: Temporal Expression Profiles Of Bombyx Mori Papain Genesmentioning
confidence: 83%
“…Our data showed that most silkworm papain-like cysteine proteases genes are highly expressed in metamorphosis not only in wandering stage involving in molting and metamorphosis 17,18 but also in later pupa stage and adult cuticle formation stage, which are highly correlated to the digestion time scale of B. mori arylphorin in vivo [ Fig. 5(D)].…”
Section: Temporal Expression Profiles Of Bombyx Mori Papain Genesmentioning
confidence: 83%
“…RNAi mediated by dsRNA ingestion requires higher dosage and multiple administrations until the onset of silencing in insects when compared to RNAi via injection in the haemolymph (Chen et al, 2008;Tian et al, 2009;Zhu et al, 2011), although dosages needed to elicit effect via injection in H. armigera remain measured in micrograms (Bober and Rafaeli, 2010;Cai et al, 2014;Du et al, 2012;Hou et al, 2012;Qiao et al, 2014;Sivakumar et al, 2007;Tang et al, 2012;Wang et al, 2010;Yang and Han, 2014a).…”
Section: Nucleotide Dsrna Concentrationmentioning
confidence: 99%
“…Substantial evidences in this direction are provided by the RNAi interference experiments on various cathepsin genes. On silencing CathL, a marked developmental as well as phenotypic deformation was observed like mortality prior to pupation and occurrence of chimeric H. armigera pupae (with larval head and pupal abdomen) (Wang et al, 2010). Similarly, in B. mori, inhibition of larva-pupa transition was seen on silencing of CathB (Wang et al, 2008); and delayed or abnormal pupation in the case when CathD genes were suppressed (Gui et al, 2006).…”
Section: Cathepsins In Insect Biotic and Abiotic Stress Responsementioning
confidence: 93%
“…Programmed cell death (PCD) of the fat body cells during metamorphosis in H. armigera is dependent on CathL. In CathL silenced lines, the expression of apoptosis effector gene caspase-1 decreased while the apoptosis inhibitor gene survivin was upregulated, suggesting that Ha-CathL regulates the apoptotic process in the fat body cells (Wang et al, 2010). Hemocyte specific expression of CathL explains that it might be involved in the autophagy of degraded fat body cells from the hemolymph since it is significantly active in the granulocytes and plasmatocytes, which are the main phagocytic cells (Wang et al, 2010;Wood and Jacinto, 2007).…”
Section: Role In Apoptosis and Autophagymentioning
confidence: 99%
See 1 more Smart Citation